Die Narratiewe Funksie van die Liedere in Openbaring 4:1-5:15 - Du Rand, Jan A. (Verbum et ecclesia, 1991)
The Narratological Function of the Hymns in Revelation 4:1-5:15 The problem is that research on the hymns in the book of Revelation has concentrated up till now one-sidedly on pre-textual issues and internal structure. Narrative criticism is recently proving that the Apocalypse could be treated as a full literary text. The application of narratological insights on plot development, focalisation/point of view and reader response as well as employing some insights from the socio cultural milieu enables the text as dramatic narrative to deliver its own message even more dynamically. The function of the hymns in chapters 4 and 5 is to confirm the identity of God and the Lamb, as well as that of the reader/hearer within a narratological framework.